What do we know about adult mortality and data quality in Peru? Mortality coverage levels and trends from recent decades - PISCOYA-DÍAZ, Mario; QUEIROZ, Bernardo (Papeles de Población, 2010)
Accurate knowledge of adult mortality levels and trends in the developing world is hampered by its widespread lack of complete vital registration systems. Although knowledge of infant and child mortality was once affect by the same problem, survey-based techniques have been more successful in estimating child and infant than adult mortality. The main objective of this paper is to estimate mortality rates for the population aged 5 and above, in Peru by sex. The study evaluates the degree of coverage, and corrects the level of mortality, when necessary, using different methodologies. The literature does not indicate the best method to investigate mortality data problems. Thus, the implementation of alternative methods will improve the understanding of the mortality levels and trends in Peru in recent decades.